2009
DOI: 10.1099/vir.0.007336-0
|View full text |Cite
|
Sign up to set email alerts
|

PKR acts early in infection to suppress Semliki Forest virus production and strongly enhances the type I interferon response

Abstract: The double-stranded RNA-activated protein kinase (PKR) is a key regulator of protein translation, interferon (IFN) expression and cell survival. Upon infection of vertebrate cells in continuous culture, the alphavirus Semliki Forest virus (SFV) initiates apoptosis and IFN synthesis. To determine the effect of PKR on SFV infection, we studied the course of infection in wild-type (wt) mice, mice with a genetic deletion of PKR (PKR−/−) and mouse embryo fibroblasts (MEFs) derived from these mice. In MEFs, PKR dela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
59
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 62 publications
5
59
1
Order By: Relevance
“…4D). This is not surprising as CHIKV is known to be cytopathic (22), similar to other alphaviruses with continual cell death in the in vitro cultures between 24 and 48 hpi (33,34). However, it is worth mentioning that a large fraction of human monocytes (up to 60%) in the mock-infected cultures also died over the 48-h period in culture conditions devoid of macrophage growth factors (35)(36)(37).…”
Section: In Vitro Infection Of Whole Blood From Healthy Donors With Cmentioning
confidence: 96%
“…4D). This is not surprising as CHIKV is known to be cytopathic (22), similar to other alphaviruses with continual cell death in the in vitro cultures between 24 and 48 hpi (33,34). However, it is worth mentioning that a large fraction of human monocytes (up to 60%) in the mock-infected cultures also died over the 48-h period in culture conditions devoid of macrophage growth factors (35)(36)(37).…”
Section: In Vitro Infection Of Whole Blood From Healthy Donors With Cmentioning
confidence: 96%
“…Firstly, interferon regulates HBV DNA replication by both immunomodulatory [4] and directly antiviral mechamism. Furthermore, as far as direct antiviral mechamism is concerned, except for HBV IRE-dependant pathway, interferon has the potential to trigger the activation of other multiple noncytolytic intracellur antiviral pathways that can target many steps in the viral life [2,11,12,23]. In a word, multiple mechanisms might be involved in antiviral effect by interferon on HBV, and IRE-dependant mechanism investigated in our present study was one of them.…”
Section: Discussionmentioning
confidence: 74%
“…Alphaviruses are very sensitive to the action of type I IFNs, and it would be reasonable to think that expression of these cytokines from such a recombinant vector could hinder its production and activity. 31,32 On the other hand, alphaviruses induce the release of type I IFNs in infected cells and expression of more IFNa from the vector may be redundant for therapeutic purposes. 31,32,36 In spite of these potential drawbacks, we have shown that it is possible to produce high titers of recombinant SFV vectors expressing IFNa in BHK cells.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 On the other hand, alphaviruses induce the release of type I IFNs in infected cells and expression of more IFNa from the vector may be redundant for therapeutic purposes. 31,32,36 In spite of these potential drawbacks, we have shown that it is possible to produce high titers of recombinant SFV vectors expressing IFNa in BHK cells. The most likely explanation for achieving this high SFV-IFN production is the fact that BHK cells have been shown to be defective in type I IFN responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation